Anti-Inflammatory Therapeutic Potential of Papaya Root Waste Extract with an Innovative Dermatological Approach - Lisma Luciana; Yulidar; Rita Sunartaty; Rizki Andalia (Postgraduate, University of Mataram, 2025)
Papaya (Carica papaya L.) is a tropical plant known for its various health benefits. Almost all parts of this plant, including its roots, contain phytochemical compounds such as flavonoids, alkaloids, saponins, and papain enzymes with potential anti-inflammatory properties. This study aimed to develop an anti-inflammatory cream based on papaya root waste extract, providing a natural therapeutic solution for skin inflammation. Papaya roots were obtained from Laweung, Pidie Regency, and processed using maceration with 96% ethanol solvent, yielding an extract with a 26% recovery rate. Phytochemical analysis revealed the presence of flavonoids, phenolics, tannins, alkaloids, terpenoids, and saponins.The cream formulation was developed with varying extract concentrations: F0 (control), F1 (1.2 g), F2 (1.6 g), and F3 (2.0 g). Based on organoleptic testing, the cream formulations showed good stability in terms of color, aroma, and texture during storage. The added rose oil provided a pleasant fragrance that meets the SNI cosmetic standards. The pH test results indicated that all formulations (F0 to F3) were within the safe range for skin application, between 5.2 and 6.4. Formula F3 had the lowest pH (5.2), but it still complied with the SNI standard. The spreadability test showed varying results, with F0 having the highest spreadability (8.1 cm), while formulas with papaya extract (F1 to F3) showed spreadability ranging from 6.06 to 7.1 cm. The viscosity of the cream increased with higher extract concentrations, with F0 having the lowest viscosity (10,000-10,800 cPs) and F3 the highest (19,000 cPs). Homogeneity testing confirmed that all formulations had uniform distributions without phase separation. In conclusion, the cream based on papaya root waste extract has potential as a natural anti-inflammatory product with physicochemical stability suitable for topical use and adds value to plant waste.